Intelligent Blockchain System Based on Differential Privacy. Issue 1 (1st February 2022) - Wu, Z J; Dai, H; Yuan, Y K; Meng, D
Abstract: Due to the advantages of decentralization, traceability and non deletion, blockchain technology can be well combined with differential privacy algorithm to protect data privacy. Therefore, it effectively ensures the privacy security of data stored in the system in terms of technical structure and algorithm. This paper proposes a micro service system architecture based on super ledger fabric, which carries out data privacy noise processing combined with smart contract, and carries out different noise processing according to the security level recognized by the system at the time of user registration. The implementation and test results of the system show that the system architecture has good scalability, traceability and security, can meet the query control of users for data privacy, and effectively prevent the tampering and destruction of data by malicious attackers.